Role and place of technical in the criminal procedure evidence - Рибалко, Жанна Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The paper analyzes the role and place of means of criminal evidence. Formulated the concept of the use of technical means for the implementation of the Criminal Procedure Evidence. Studied the stages of proof on which the application of technical means possible or necessary. Identified areas for further research on the issues discussed.